PROFESSOR AHMAD FARHAN BESTOWED ROAD SAFETY ICON AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 1 April 2015 The Dean of the School of Civil Engineering, Universiti Sains Malaysia (USM), Professor Dr. Ahmad Farhan Mohd Sadullah has been chosen by the Malaysian Road Transport Department (JPJ) as the Road Safety Icon for his contributions in the study and implementation of road safety programmes.